Effectiveness of training stop‐smoking advisers to deliver cessation support to the UK national proposed standard versus usual care in Malaysia: a two‐arm cluster‐randomized controlled trial - Wee, Lei Hum; West, Robert; Tee, Guat Hiong; Yeap, Lena; Chan, Caryn Mei Hsien; Ho, Bee Kiau; Perialathan, Komathi; Nik Mohamed, Mohamad Haniki; Michie, Susan; Jackson, Sarah E. (Wiley, 2021)
To assess the effectiveness of training stop smoking services providers in Malaysia to deliver support for smoking cessation based on the UK National Centre for Smoking Cessation and Training (NCSCT) standard treatment programme compared with usual care.